Rest and Soap Comparison on Web Service Technology for Android Based Data Services - Kusumaningrum, Anggraini; Sajati, Haruno; Anarianto, Donny (SENATIK STT Adisutjipto, 2019)
Comparison between ReST API and SOAP web services in providing data services that are carried out to support the improvement of these web services. The data tested is divided into 2, namely data with the same size format and data with different size formats. The test is divided into 3 stages, the first collecting with 10 data, the second 20 data, and the third 30 data, by carrying out data loading from each comparing web service. From the overall results obtained from the ReST API runs faster than SOAP. With an overall total data collection time on different devices with the same size format in the ReST API it produces 3.4 seconds and SOAP produces 3.9 seconds. While receiving data on different devices with different size formats on the ReST API, it takes 4.7 seconds and SOAP takes 5.3 seconds.